Methodological basis of cultural institutions studies - I. I. Maslikova, (Ukrainian Cultural Studies, 2020)
The article deals with the "atomistic", "holistic", "teleological" theories of social institutions, which form the methodological basis for the Cultural Institutions Studies. The "atomistic" theories of institutions (D. North, D. Hodgson, E. Ostrom) relate to the conclusions of the institutional economics put emphasize on the importance of certain normative models and frameworks of social behavior, which are the institutions. Representatives of the "holistic" theories of institutions (G. Spencer, E. Durkheim, T. Parsons) highlight the connection between institutions ("structures") and their contribution to a society ("function"), and distinct institution are described as interdependent and necessary for functioning of the society in general. Representatives of the "teleological" approach in explaining the essence of social institutions (P. Gielen, S. Miller, Ch. Taylor, etc.) focus on the realization of a common goal, which is a set of interrelated individual goals, which are perceived by distinct individuals as their personal goal, but which makes sense only in the interaction of all participants of joint actions. Such actions most find their expression in the cultural sphere: team games, dances, theatrical performances, musical events, academic activities, etc.Recourse to these concepts allows us to outline the problematic field of cultural institutions studies as a research area, which is based on the latest investigation in cultural studies, sociology, and cultural economics. The main tasks of cultural institutions studies are related to the creation of descriptions of institutional practices, the elucidation of the patterns of functioning of cultural institutions, the prediction of future changes in institutional cultural practices in the context of cultural economy and cultural policy.In consideration of the basic approaches to the definition of a social institute, the essential characteristics of a cultural institute are revealed, which are manifested in three aspects: normative and regulatory aspect (complex of values, norms, rules), behavioral and procedural aspect (behavioral models, institutional roles, forms of joint interaction), organizational aspect (cultural institutions that produce, preserve and promote cultural good).
Keywords: Cultural Institutes Studies, social institution, joint activity, social practices, Cultural Economics, cultural economy, and cultural policy